Phyllantin Extraction Using Imidazolium Ionic Liquids with Chloride and Bromide Anion by Microwaved Assisted Extraction Method - Babay Asih Suliasih; Surya Geraldi; Hana Yunita Hidayat; Abdul Mun'im; Eko Aditya Rifai (Pusat Inovasi Sains, 2023)
Phyllanthin is known to have therapeutic properties such as immunomodulator, nephroprotective, and anticancer. Phyllanthin is a lignan compound that is commonly found in plants of the Phyllanthus genus, one of which is green meniran (Phyllanthus niruri). Solvent Ionic Liquid (IL) is one of the alternative solvents that are widely used for the extraction of compounds from a plant. The purpose of this study were to compare the extraction yield of philanthine compounds from meniran herbs using IL solvent by Microwave Assisted Extraction (MAE) with methanol by maceration method, and to determine the IL solvent that could produce the highest phyllanthin content. Optimization were carried out using the independent variables IL solvent concentration (0.25 M, 0.75 M, and 1.25 M) and sample-solvent mixture (1:10, 1:12, and 1:14). The variable modeling is designed using Response Surface Methodology that produced 9 runs of combination of solvent concentration and sample-solvent mixture ratio. The phyllanthin assay was using High Performance Liquid Chromatography (HPLC) with ethanol-water mixture (66:34) as mobile phase and wavelength at 229 nm for detection. The optimum extraction conditions showed the best results for imidazolium chloride IL at 1st run with a concentration of 0.75 M, the sample-solvent mixture of 1:14 and phyllanthin content of 0.1783 mg/g while imidazolium bromide IL at 7th run with a concentration of 0.75 M and the sample-solvent mixture of 1:12 and phyllanthin content of 0.23 mg/g. However, the methanol maceration method could only extract phyllanthin as much as 0.1319 mg/g. Based on these results, the use of IL-MAE was more effective than the methanol maceration method due to higher phyllantin extract.